2016
DOI: 10.1093/mnras/stw2583
|View full text |Cite
|
Sign up to set email alerts
|

The no-spin zone: rotation versus dispersion support in observed and simulated dwarf galaxies

Abstract: We perform a systematic Bayesian analysis of rotation vs. dispersion support (v rot /σ) in 40 dwarf galaxies throughout the Local Volume (LV) over a stellar mass range 10 3.5 M < M < 10 8 M . We find that the stars in ∼ 80% of the LV dwarf galaxies studied -both satellites and isolated systems -are dispersion-supported. In particular, we show that 6/10 isolated dwarfs in our sample have v rot /σ 1.0, while all have v rot /σ 2.0. These results challenge the traditional view that the stars in gas-rich dwarf irre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
104
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 152 publications
19
104
1
Order By: Relevance
“…In the aforementioned scenario, transition-type dwarfs should possess appreciable stellar rotation, having been only partially transformed. Although recent studies have reported significant rotation in both Pegasus (Wheeler et al 2017) and Phoenix (Kacharov et al 2017) with V rot /σ * ≈1, irrefutable evidence…”
Section: Discussionmentioning
confidence: 99%
“…In the aforementioned scenario, transition-type dwarfs should possess appreciable stellar rotation, having been only partially transformed. Although recent studies have reported significant rotation in both Pegasus (Wheeler et al 2017) and Phoenix (Kacharov et al 2017) with V rot /σ * ≈1, irrefutable evidence…”
Section: Discussionmentioning
confidence: 99%
“…The gas velocity dispersion as a function of galaxy mass is estimated following the theoretical disk instability arguments from W15, in conjunction with the empirical trends of gas fraction as a function of galaxy stellar mass, M * from Whitaker et al (2014). Specifically at redshift zero, …”
Section: Appendix B: Analytic Mass Dependent Ism Cooling and Gmc Scatmentioning
confidence: 99%
“…Whereas there is little evidence for systemic rotation in dSph galaxies, a number of dIrr (or at least their gas and young stars) show clear signs of ordered rotation, at least in their gas component and young stars (e.g., Leaman et al 2012;Kirby et al 2014). Although finding rotating subcomponents in a dSph would be harder than in dIrr, where recently-formed stars are more easily identified, it is generally agreed that the kinematic evidence suggests a scenario where some event in the past history of dSphs has been responsible for both terminating their star formation and for reducing the importance of centrifugal support (see, however, Wheeler et al 2015, for a more nuanced view).…”
Section: Introductionmentioning
confidence: 99%